The influence of pressure and thinner on the bonding properties of adhesives to metal and composite materials. Issue 1 (October 2020) - Li, Qinghua; Tian, Ranran; Zhang, Yan; Zeng, Yu; Zhao, Ming
Abstract: In order to judge the influence of pressure and thinner on the bonding shear strength of composite material and metal, the experiment uses different proportions of thinner epoxy resin to impregnate 3K 240G carbon fiber cloth; Kevlar fiber is subjected to different curing pressures the 45 steel specimens bonded with cloth composite materials were cured at high temperature. Through the international standard ISO1747-1976 determination of the adhesive shear strength of vulcanized rubber and rigid metal plate-four-plate shear method, the shear strength of specimens under different proportions of thinner and different curing pressures is measured. The results show that the fiber cloth composite material with the same immersion time will not increase the shear strength of the specimen when a certain pressure is applied during the bonding and curing process with the metal. At the same time, the thinner in the adhesive of the immersion fiber cloth is 10% When, better shear strength can be obtained.